2017
DOI: 10.1177/0961203317725585
|View full text |Cite
|
Sign up to set email alerts
|

Medication adherence, depression and disease activity among patients with systemic lupus erythematosus

Abstract: Introduction Medication non-adherence is an important cause of treatment failure among patients with systemic lupus erythematosus (SLE). Depression is a common neuropsychiatric disorder associated with SLE. The aims of this study are to assess the prevalence of both medication non-adherence and depressed mood among Saudi patients with SLE by using validated tools and to explore the impact of both depressive symptoms and disease activity on medication non-adherence. Methods A cross-sectional study was conducted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
26
3

Year Published

2017
2017
2025
2025

Publication Types

Select...
6
2
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 28 publications
4
26
3
Order By: Relevance
“…Consistent with the studies mentioned above, we found that SLE is a risk factor for BPPV among depressive cohort (table 4) but not for all the participants (table 3) in this study. Based on the previous studies, several results of the studies could provide the evidence revealing that the comorbidities with depressive disorder and SLE would result in the exacerbation of the SLE disease activities, no matter the possible explanations were psychological or behavioural issues such as lack of insight and poor anti-inflammatory drug compliance 48–50. The evidence indicated that the severity of inflammatory processes on the differences between the patients with depressive disorder alone and the depressive patients comorbid with SLE.…”
Section: Discussionmentioning
confidence: 96%
“…Consistent with the studies mentioned above, we found that SLE is a risk factor for BPPV among depressive cohort (table 4) but not for all the participants (table 3) in this study. Based on the previous studies, several results of the studies could provide the evidence revealing that the comorbidities with depressive disorder and SLE would result in the exacerbation of the SLE disease activities, no matter the possible explanations were psychological or behavioural issues such as lack of insight and poor anti-inflammatory drug compliance 48–50. The evidence indicated that the severity of inflammatory processes on the differences between the patients with depressive disorder alone and the depressive patients comorbid with SLE.…”
Section: Discussionmentioning
confidence: 96%
“…The challenges can include favouring disease remission, limiting the use of glucocorticoids, managing fertility and pregnancy, managing comorbidities and so on [2] . Besides, current evidence suggests that the percentage of nonadherent patients ranged from 37% to 75%, which have a remarkable correlation with depression, low education level and polypharmacy [3][4][5][6][7] . Interventions to improve adherence and management of patients have become an urgent requirement.…”
Section: Introductionmentioning
confidence: 92%
“…In addition, the retrospective nature of the study did not allow us to screen accurately for depression, a factor known to be associated with non-adherence in the general lupus population 18 . Finally, despite one of the longest recorded follow up periods exceeding 422 patient-years we only had 12 patients with graft rejection or failure, which may have impacted on identifying smaller potential associations with the other variables included in this study.…”
Section: Limitationsmentioning
confidence: 99%